Peranan Apresiasi Guru Terhadap Antusias Belajar Siswa Kelas XI Madrasah Aliyah Hasan Muchyi - Zuyyina Candra Kirana; Anifa Noor Al Badri A.M (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
This study aims to determine the urgency of giving appreciation or appreciation to students who have an active role/achievement in their quality personality. Meanwhile, on the other hand, most of the teachers do not give appreciation or appreciation to students. For this reason, the teacher's job is not only to provide directions and assignments, but it is highly recommended to appreciate students for making the students feel proud, enthusiastic and continue to develop their achievements and encourage them to make achievements. The appreciation given to students who experience failure is verbal appreciation in the form of positive words and motivation. Through field observations and individual interviews, the teacher's appreciation has proven to be very important for students' enthusiasm for learning. The practice of giving appreciation has also been applied by several teachers at Madrasah Aliyah Hasan Muchyi to their students, both those who are successful and those who fail in the process. This was proven when a student failed in a competition, he was still given the appreciation in the form of motivation and mental strengthening as well as verbal and gestural appreciation and added value during teaching and learning activities in class. is a way for teachers to appreciate the learning process of their students